Policy competition, imitation and coordination under uncertainty - Carsten Hefeker (Philipps-University Marburg, School of Business and Economics, 2022)
The paper analyzes under what circumstances policymakers experiment with policies with uncertain outcomes, when they prefer to imitate policies initiated in other countries, and when they prefer to coordinate policies internationally. Policymakers have private costs of active policies and compete internationally in a yardstick competition which gives rise to a potential distortion between what citizens want and what policymakers do. I find that policymakers' policies as well as regime choice deviate from what citizens want but that an increase in uncertainty about policy outcomes decreases this distortion.
Keywords: D78; F42; F59; 330; Uncertainty; policy competition and coordination; yardstick competition